Creativity and learning through electronic group causal mapping. (14th October 2004) - Shaw, Duncan
This paper proposes, and begins to evaluate, a format of brainstorming-type activity which aims to release the creativity of participants and encourage them to learn about a wider range of issues in more detail. The format does this through providing a two-stage brainstorming session. After the first brainstorm, participants have an opportunity to both piggy-back off other peoples ideas (i.e. create new ideas by synthesising other peoples' ideas into their own perspectives), and share causal links to build a causal map with the brainstormed ideas. Five causal mapping sessions with organisations have been analysed. Findings suggest that ideas shared when piggy-backing are often highly creative and unique for the participant who shared them. Also piggy-backing and causal linking seem to provide effective opportunities for individual learning as participants have time to reflect upon other peoples' perspectives and share their own views on those.